The psiconeural relation in stress or from neurons to social cognition: an empirical review - Campos Roldán, Manuel (2007)
It reviews the brain activity, facts perception-appraisal, social context and neural mechanisms related in stress processes. In this paper, that sequence defines the psychoneural relation, situated in the prefrontal cortex and thalamus dorsomedial-amygdala circuit.